PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SOAL ASESMEN KOMPETENSI MINIMAL (AKM) YANG VALID DAN RELIABEL MELALUI PROSES PENDAMPINGAN BERKELANJUTAN DI SMP NEGERI 4 KALIKAJAR PADA SEMESTER GENAP TAHUN PELAJARAN 2021/2022 - Kustriyono, Kustriyono (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
This study aims to: (1) escort and assist the teachers of SMP Negeri 4 Kalikajar in compiling a package of Daily Assessment questions (PH) in the form of a Minimum Competency Assessment (AKM) in order to obtain valid and reliable item items, (2) find out how big the success rate of mentoring senior teachers on the percentage of improving the quality of the Daily Assessment question package (PH) in the form of AKM. This study used the Classroom Action Research (CAR) method with 2 cycles, where the research subjects were all subject teachers. The data analysis used is descriptive comparative, where this analysis is used to compare the result tables for the quality of PH question packages. The results showed that: (1) based on qualitative analysis of PH questions, it was found that there was an increase in the percentage from 18.57% in cycle 1 to 74.29% in cycle 2, (2) based on quantitative analysis of PH questions, the result was also an increase in the percentage from 58.57% in cycle 1 to 74.29% in cycle 2, (3) For teachers who teach linear with their S1 diploma, the percentage of PH 2 questions that are